From Family Values to Mate Selection: A Gender Moderation Study - Amatulah, Dinda Ayu Safira; Rohmah Nurhayati, Siti (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
The background of this study is grounded in the shifting values of modern society, where individuals often experience conflicts between personal preferences and traditional family values. In the context of mate selection, family values remain an important factor that can influence individual decisions, even though personal freedom in choosing a partner is increasingly emphasized in contemporary times. Furthermore, gender is considered relevant as a moderating variable due to differences in how men and women interpret family values and determine their partner preferences. Based on this context, the present study aims to examine the influence of family values on mate selection preferences among emerging adults, as well as to explore the role of gender as a moderating variable. This research employed a quantitative method with a survey approach involving 385 emerging adult respondents (aged 20–40 years, unmarried, and residing in Indonesia). The instruments used were the Family Values Scale and the Mate Selection Preference Scale, both of which had been tested for validity and reliability. Data were analyzed using moderation regression. The findings revealed that family values had a significant effect on mate selection preferences, and gender moderated this relationship. These results highlight the importance of considering family values and gender in the formation of mate selection preferences. The implications of this study are directed toward individuals, counselors, parents, and policymakers in designing premarital readiness programs.Latar belakang penelitian ini didasarkan pada pergeseran nilai dalam masyarakat modern, di mana individu sering kali mengalami konflik antara preferensi pribadi dan nilai tradisional keluarga. Dalam konteks pemilihan pasangan, nilai-nilai keluarga tetap menjadi faktor penting yang dapat memengaruhi keputusan seseorang, meskipun kebebasan memilih semakin ditekankan pada era kontemporer. Selain itu, jenis kelamin dipandang relevan sebagai variabel moderator karena adanya perbedaan pandangan antara laki-laki dan perempuan dalam memaknai nilai keluarga dan menentukan pilihan pasangan. Berdasarkan hal tersebut, penelitian ini bertujuan untuk mengkaji pengaruh nilai-nilai keluarga terhadap preferensi pemilihan pasangan pada dewasa awal, serta menelaah peran jenis kelamin sebagai variabel moderator. Penelitian ini menggunakan metode kuantitatif dengan pendekatan survei terhadap 385 responden dewasa awal (usia 20–40 tahun, belum menikah, dan berdomisili di Indonesia). Instrumen yang digunakan adalah skala nilai-nilai keluarga dan skala preferensi pemilihan pasangan yang telah diuji validitas dan reliabilitasnya. Analisis data dilakukan dengan regresi moderasi. Hasil penelitian menunjukkan bahwa nilai-nilai keluarga berpengaruh signifikan terhadap preferensi pasangan, dan jenis kelamin memoderasi hubungan tersebut. Temuan ini menegaskan pentingnya mempertimbangkan nilai-nilai keluarga dan peran jenis kelamin dalam pembentukan preferensi pasangan. Implikasi penelitian ditujukan bagi individu, konselor, orang tua, dan pembuat kebijakan dalam merancang program kesiapan pernikahan.